Discriminating language rights and politics in the post-Yugoslav states - Pupavac, Vanessa (Taylor & Francis, 2006)
Pupavac examines the rise of linguistic human rights advocacy and its approach in a case study of language politics in the post-Yugolav states. A core concern of contemporary linguistic rights advocacy has been to tackle ethnically based discrimination and promote ethnic diversity. It does not only seek to prevent states from discriminating against those who speak minority languages. It expects states to take positive steps to preserve their diversity of languages. However strategies affirming distinct linguistic identities may become complicit in perpetuating ethnic discrimination and ethnic divisions, as is evident in the language politics of the post-Yugoslav states.